Facing a slithery dragon: systematics of the Petracola ventrimaculata (Boulenger, 1900) species complex (Squamata: Gymnophthalmidae) with description of five new species - Echevarría, Lourdes Y.; Venegas, Pablo J.; García-Ayachi, Luis A.; Bravo, Antonio García-; Torres-Carvajal, Omar (Zootaxa, 2026)
Nearly two decades ago, the gymnophthalmid lizard Petracola ventrimaculata was hypothesized to be a species complex based on dorsal and ventral color pattern differences among populations within a wide and disjunct geographical area in the northern Peruvian Andes. Here, we address this proposal using both molecular and morphological evidence. We analyzed a molecular matrix of Cercosaurinae, including 22 specimens and 78 DNA sequences of P. ventrimaculata sensu lato to study the phylogenetic relationships among its populations. We also conducted a detailed examination of the external morphology of 236 P. ventrimaculata specimens from several populations. Based on our analyses, we describe five new Petracola species, two of them previously assigned to P. ventrimaculata, from Cordillera Occidental and Cordillera Central in northern Peru. P. ventrimaculata sensu stricto is distributed across several localities in Cajamarca department in the northern part of the Cordillera Occidental in northwestern Peru. We hypothesize that the distribution patterns within the Petracola ventrimaculata species complex could be related to vicariant processes driven by the complex orogeny of the Huancabamba Depression and the Marañón River valley. Given its distinctive morphological traits and disjunct distribution, we recommend treating P. labioocularis as incertae sedis within Cercosaurinae, pending molecular data to resolve its phylogenetic placement. We present recommendations for future descriptions of new species of Petracola.